ChemInform Abstract: An Easy Access to Tertiary Amides from Aldehydes and N, N‐Dialkylchlorothiophosphoramidates. Issue 39 (23rd September 2014) - Pathak, Uma; Bhattacharyya, Shubhankar; Pandey, Lokesh Kumar; Mathur, Sweta; Jain, Rajeev
Abstract The reaction of benzaldehyde with 2‐methylpiperidine does not give the desired product.